An Acute Care Contingency Management Program for the Treatment of Stimulant Use Disorder: A Case Report. Issue 6 (December 2020) - Bach, Paxton; Garrod, Emma; Robinson, Kaye; Fairbairn, Nadia
Abstract : Background: Illicit stimulants such as crystal methamphetamine and cocaine are a rising cause of morbidity and mortality in North America. Unfortunately, there are few evidence-based approaches for the management of stimulant use disorder. Contingency management programs are currently the best evidenced treatment strategy, designed to reward behavior change and offer competing reinforcers toward the goal of reducing substance use, but these programs are often difficult to access. Given that it is well understood that hospitalization presents a valuable opportunity for the initiation of treatment for a variety of substance use disorders, the adaptation of contingency management programs to an acute medicine inpatient setting is a potentially viable option to improve care, and to increase access to effective treatment for stimulant use disorders. Case Summary: We present a case outlining the clinical care of a complex medical patient admitted with osteomyelitis, whose course in hospital changed significantly upon enrollment in a pilot contingency management program in an urban hospital in Canada. Discussion: This case illustrates how effective treatment programs can be adapted as needed for use in novel settings, especially where current options are inaccessible, inadequate, or ineffective.